Bottleneck links, essential intermediaries, and competing paths of diffusion in networks - Mihai Manea (Theoretical Economics, 2021)
We investigate how information goods are priced and diffused over links in a network. A new equivalence relation between nodes captures the effects of network architecture and locations of sellers on the division of profits, and characterizes the topology of competing (and potentially overlapping) diffusion paths. Sellers indirectly appropriate profits over intermediation chains from buyers in their equivalence classes. Links within the same class constitute bottlenecks for information diffusion and confer monopoly power. Links that bridge distinct classes are redundant for diffusion and generate competition among sellers. In dense networks, competition limits the scope of indirect appropriability and intellectual property rights foster innovation.
Keywords: C78; D85; L14; O33; 330; Networks; diffusion; indirect appropriability; captive markets; intermediation; competition; bottlenecks; redundant links; information goods; copying; intellectual property